PERTIMBANGAN “UNSUR MASYARAKAT” DALAM PENYELESAIAN PERKARA PIDANA MELALUI KEADILAN RESTORATIF DI KEJAKSAAN DALAM PERSPEKTIF SOSIOLOGI HUKUM - Prakoso, Airlangga Surya; Nurcahyono, Arinto (Penerbit Universitas Atma Jaya Yogyakarta, 2025)
One development in the Indonesian law enforcement system is the implementation of restorative justice in the termination of criminal cases. One method of resolving criminal cases through restorative justice in the Indonesian law enforcement system is the Republic of Indonesia Attorney General's Office, based on Attorney General Regulation No. 15 of 2020 concerning the Termination of Prosecution Based on Restorative Justice. Considerations for resolving prosecutions at the Attorney General's Office stage require a review of the impact of the application and considerations of restorative justice, based on legal developments in society, which can be analyzed using a sociological legal perspective. The purpose of this legal paper is to analyze the resolution of criminal cases through restorative justice in the Attorney General's Office from a sociological legal perspective. This paper utilizes empirical research methods. The conclusion of this legal paper is that consideration of community elements in resolving cases through restorative justice in the Attorney General's Office is crucial. This is because the Attorney General's Office implements a profiling system from the Intelligence Division to directly engage with and solicit or gather information from the public. In this case, the public plays a role in providing information related to the realities of the community surrounding the suspect. The review of restorative justice uses a sociological perspective of law, including an examination of the function of law as a tool for societal change related to the impact of regulations on society. Considerations for resolving criminal cases in the Prosecutor's Office through restorative justice can be explained from a sociological perspective of law, relating to the law's role as social control, a tool for law enforcement, and a tool for social change.